The Use of YouTube and TikTok in Improving the Students’ Vocabulary Achievement - Juliana, Devi; Tambunan, Anna Riana Suryanti; Pane, Isli Iriani Indiah (Journal of English for Academic and Specific Purposes (JEASP), 2024)
This study discussed the applications of YouTube and TikTok to students’ vocabulary achievement. It was aimed to describe the students' vocabulary achievements when taught using the YouTube application, to elaborate on the student's vocabulary achievements when they are taught using the TikTok application, and to discover the differences in the effect of implementing the YouTube and TikTok applications on the students’ vocabulary achievement. This research used experimental research with a quantitative approach. Eighty students were taken as the sample. They were divided into 40 students for the experimental 1 group and 40 students for the experimental 2 group. The data was collected from observation, interviews, and vocabulary tests. Based on the results, it was found that YouTube applications significantly affect the students’ vocabulary achievement. It showed an improvement of about 35 % in the experimental 1 pretest group; the students who passed the KKM were nine stuents (22.5%).  In experiment 1 post-test group, there was an improvement in students’ scores, where 23 students, or 57.5%, passed KKM. This means that YouTube application affects 35% of students' vocabulary achievement. On the other hand, the TikTok application also significantly affects the students’ vocabulary achievement. In the pretest results, only four students (10%) who passed the KKM. However, in the posttest results, the students got around 90% improvements. In other words, based on the posttest results in the experimental 2 group, all students passed the KKM (100%). Thus, based on the hypothesis calculation, it can be concluded that TikTok significantly affects students’ vocabulary achievement. It is proven from tcalculating t table or 2.469 1.683/. It means that Ho is rejected and Ha is accepted.